Pengelolaan Karakter Green-Behavior Pada Generasi Milenial Dalam Meningkatkan Minat Penggunaan Green-Product - Ni Kadek Mita Ayu Wandari; Gede Sri Darma (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2021)
This study aims to manage the character of green-behavior for millennial generation in increasing interest in using green-products. This research indicates that how to manage and implement green-behavior characters for millennial generation in increasing interest in using green-products: (1) Green-behavior character is about how to manage the character of the millennial generation to generate interest in using green-products; (2) The character of green-behavior refers to the awareness of the millennial community in Denpasar City to have a high sense of concern of environment; (3) The implementation of the green-behavior character is carried out to help government jointly protect the environment.